If everything is relative, then that everything is relative, is also relative. Is global relativism dead? - Pietraszek, Marta (Hybris, 2019)
Global relativism, with its claim that everything is relative, is one of the most harshly criticized concepts in the history of philosophy. The strongest argument against it has been the argument from self-refutation ascribed originally to Plato. The paper presents strong and weak version of the argument in order to show the one that is best suited for the way of reasoning characteristic to the antique period and so that it shows that Plato’s argument against global relativism ought to be treated rather in dialectical than logical way. Consequently, it weakens the power of argument formulated in Plato’s Thaetetus and confutes the widely spread interpretation of it.